Scientific delusions [elektronička građa] - Tomljenović, Ana (2011)
After Freud, in his essay „Psychoanalytic Notes on an Autobiographical Account of a Case of Paranoia“ (1910), provided an exhaustive analysis of the autobiographical notes of the German judge Daniel Paul Schreber entitled „Memoirs of My Nervous Illness“ (1903), he perceived a remarkable similarity between the development of Schreber‘s delusional system and his own psychoanalytic theory. Elaborating Freud‘s idea that in pursuit of the totality of knowledge and the certainty of cognition the scientist is most similar to the paranoid, Jacques Lacan, on the basis of the same autobiography, constructs the theory of psychosis, which according to Ellie Ragland Sullivan represents Lacan‘ s most important contribution to psychoanalysis, linguistics, literary theory and philosophy. Relying on the thesis that every organisation of knowledge corresponds to a paranoid strategy, the paper raises the question of whether a 'healthier approach' to science exists. Psychoanalytic theory, in this sense, points us in the direction of fiction, emphasizing that it is precisely fictionalisation that offers us knowledge on the incompleteness of knowledge – negative knowledge – the only kind that is not crazy.